Intelligent high-tech coating of natural biopolymer layers - Murtaja, Yousef; Lapčík, Lubomir; Lapčíková, Barbora; Gautam, Shweta; Vašina, Martin; Spanhel, Lubomir; Vlček, Jakub (Advances in colloid and interface science, 2022)
Polymeric materials play a vital role in our daily life, but the growing concern for the environment demands economical and natural biopolymers that can be cross-linked to create technologically innovative lightweight materials. Their cellular matrix with extreme flexibility makes them highly acceptable for application prospects in material science, engineering, and biomedical applications. Furthermore, their biocompatibility, mechanical properties, and structural diversity provide a gateway to research them to form technologically important materials. In the light of the same, the review covers cellulose derivatives. The first section of the study covers the general properties and applications of cellulose and its derivatives. Then, the biopolymers are characterised based on their dielectric properties, crystallinity, rheology, and mechanical properties. An in-depth analysis of the diffuse process of swelling and dissolution followed by a brief discussion on diffusion and diffusion of crosslinking has been done. The review also covers a section on swelling and swelling kinetics of carboxymethyl cellulose (CMC) and hydroxyethyl cellulose (HEC). The examination of all the aforementioned parameters gives an insight into the future aspects of the biopolymers. Lastly, the study briefly covers some preferred choices of cross-linking agents and their effect on the biopolymers.
Keywords: Carboxymethylcellulose Sodium; sodná sůl karboxymethylcelulosy; reologie; biopolymery; Thermodynamics; Cellulose; Diffusion coefficient; Hydrogels; Hydrogel swelling; Crosslinking; Biopolymers; Rheology; celulosa; hydrogely